ANÁLISE DA VARIABILIDADE ESPAÇO TEMPORAL DA CHUVA MENSAL NO ESTADO DE PERNAMBUCO UTILIZANDO O MÉTODO ENTROPIA DE PERMUTAÇÃO - FERREIRA, Diego Vicente de Souza; SILVA, Antonio Samuel Alves da; STOSIC, Tatijana; MENEZES, Rômulo Simões Cezar; IRMÃO, Ricardo Alexandre; SOUZA, Wanderson Santos (Brazilian Journal of Biometrics, 2018)
In this work, we analyze spatial variability of rainfall dynamics on monthly scale, in the state of Pernambuco, Brazil, using Permutation Entropy. This method was introduced as a complexity measure for temporal series, considering time causality trough the symbolization technique based on comparison of neighboring values in a time series. The results show that the entropy values decrease with distance from the coast, indicating greater variability and less predictability of monthly rainfall in the regions Zona de Mata and Agreste, and smaller variability and higher predictability of monthly rainfall in the regions Sertao and Sao Francisco Valley.